Murder most Russian: true crime and punishment in late imperial Russia - McReynolds, Louise (Cornell University Press, 2013)
"How a society defines crimes and prosecutes criminals illuminates its cultural values, social norms, and political expectations. In Murder Most Russian, Louise McReynolds uses a fascinating series of murders and subsequent trials that took place in the wake of the 1864 legal reforms enacted by Tsar Alexander II to understand the impact of these reforms on Russian society before the Revolution of 1917. For the first time in Russian history, the accused were placed in the hands of juries of common citizens in courtrooms that were open to the press. Drawing on a wide array of sources, McReynolds reconstructs murders that gripped Russian society, from the case of Andrei Gilevich, who advertised for a personal secretary and beheaded the respondent as a way of perpetrating insurance fraud, to the beating death of Marianna Time at the hands of two young aristocrats who hoped to steal her diamond earrings"--Publisher's Web site